Poly(β-amino ester)s-based nanovehicles: Structural regulation and gene delivery - Zhang, Jiayu; Cai, Xiaomeng; Dou, Rui; Guo, Chen; Tang, Jiaruo; Hu, Yi; Chen, Hanqing; Chen, Jun (Molecular therapy. Nucleic acids, 2023)
The first poly(β-amino) esters (PβAEs) were synthesized more than 40 years ago. Since 2000, PβAEs have been found to have excellent biocompatibility and the capability of ferrying gene molecules. Moreover, the synthesis process of PβAEs is simple, the monomers are readily available, and the polymer structure can be tailored to meet different gene delivery needs by adjusting the monomer type, monomer ratio, reaction time, etc. Therefore, PβAEs are a promising class of non-viral gene vector materials. This review paper presents a comprehensive overview of the synthesis and correlated properties of PβAEs and summarizes the progress of each type of PβAE for gene delivery. The review focuses in particular on the rational design of PβAE structures, thoroughly discusses the correlations between intrinsic structure and effect, and then finishes with the applications and perspectives of PβAEs. [Display omitted] Chen and colleagues evaluate poly(β-amino) esters (PβAEs) as a promising non-viral gene vector material, discussing their simple synthesis, diverse monomers, and customizable structure for various gene delivery needs. Additionally, the review explores intrinsic structure-effect correlations through rational design and concludes by discussing PβAEs' applications and future prospects.